2004
DOI: 10.1038/sj.onc.1207507
|View full text |Cite
|
Sign up to set email alerts
|

Strong synergy between mutant ras and HPV16 E6/E7 in the development of primary tumors

Abstract: E6/E7 oncogenes of high-risk human papilloma virus (HPV) subtypes are essential for the development of certain types of cancers. However, these oncogenes are insufficient to transform normal cells into an immortalized or malignant state. Mutant Ha-ras cooperates with E6/E7 of HPV subtype 16 in transformation of cells in vitro and may contribute to some HPV-associated cancers in humans. This study investigates whether HPV16 E6/E7 and v-Ha-ras synergize in vivo. FVB/n mice transgenic for v-Ha-ras gene (R þ ) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 52 publications
(53 reference statements)
3
35
0
Order By: Relevance
“…We hypothesized that other cellular changes are required to support invasive growth in vivo. The idea that cells would require another mutation or oncogene for neoplastic growth is supported by the observation that Ras signaling is frequently aberrant in HNSCC; furthermore, in past studies Ras has been shown to act synergistically with E6 in mouse skin cancer models (23,24,32,36 (Fig. 1C), although it is possible that E6 alters the downstream signaling of Ras pathways.…”
Section: E6 Induces Aig In Mtecs Via a Pdz-dependent Mechanismmentioning
confidence: 91%
“…We hypothesized that other cellular changes are required to support invasive growth in vivo. The idea that cells would require another mutation or oncogene for neoplastic growth is supported by the observation that Ras signaling is frequently aberrant in HNSCC; furthermore, in past studies Ras has been shown to act synergistically with E6 in mouse skin cancer models (23,24,32,36 (Fig. 1C), although it is possible that E6 alters the downstream signaling of Ras pathways.…”
Section: E6 Induces Aig In Mtecs Via a Pdz-dependent Mechanismmentioning
confidence: 91%
“…Ras activation upregulated the gene expression levels of E6 and E7 (34). Ras was reported to contribute to cellular transformation in cooperation with E6 and E7 in the mouse model (19,47). With clinical samples, the rate of ras mutation was reported to increase in association with the lesion's grade of cervical neoplasia (2).…”
mentioning
confidence: 99%
“…High-risk HPV strains also synergize with activation of Ras or the epidermal growth factor receptor (EGFR) to promote cell transformation in vitro (Storey and Banks, 1993;Woodworth et al, 2000) and tumourigenesis in vivo (Schreiber et al, 2004). These data, combined with the observed loss of Scribble in cancers such as colon and breast Gardiol et al, 2006) prompted us to directly test whether loss of Scribble cooperates with activation of Ras in mammalian oncogenesis.…”
Section: Introductionmentioning
confidence: 99%